A PRACTICAL APPROACH TO HIGH-ALTITUDE ILLNESS - Bojić, Suzana (Medical Research, 2022)
At high altitudes, the human body is exposed to the low partial pressure of inhaled oxygen, the condition known as hypobaric hypoxia. When the ability of the human body to adapt to these conditions is exceeded, an Acute Altitude Illness (AAI) develops. In an AAI spectrum, Acute Mountain Sickness (AMS), High Altitude Pulmonary Edema (HAPE) and High-Altitude Cerebral Edema (HACE) are usually described. Due to the high incidence of AAI and potentially high mortality in HAPE and HACE patients, a series of prophylactic and therapeutic measures are introduced as proposed by current guidelines. The most important prevention of AAI is the low speed of ascent. Treatment of choice for HAPE and HACE is quick descent, supplemental oxygen if available, and medications such as acetazolamide, dexamethasone, nifedipine, and phosphodiesterase inhibitors.